(untitled) (Journal of Hama University, 2025)
This study aimed to determine the extent to which listed companies in Damascus Securities Exchange practice earnings management. In addition, the study aimed to test the impact of companies’ practice of earnings management on the earnings per share (EPS) of these companies’ shares. To achieve the objectives of the study and test the hypotheses, a sample of 25 listed companies in Damascus Securities Exchange was selected during the period 2019-2023. The total number of observations during the study period was (125) observations. The Modified Jones 1995 was used to determine the extent to which the study sample’s companies practice earnings management during the study period. In addition, a number of statistical methods and tools were used, such as Pearson’s correlation coefficient test, ANOVA analysis of variance, and regression analysis. The SPSS program was also used to test the hypotheses. The study reached the following results: 1- There are significant indicators of the practice of earnings management by public joint-stock companies listed on Damascus Securities Exchange during the study period (2019-2023), and the percentage of listed companies (study sample) practicing earnings management reached 81% of the total number of observations. 2- There is a significant effect of the practice of earnings management by public joint-stock companies listed on Damascus Securities Exchange on earnings per share (EPS).